Artificial neural networks and machine learning - ICANN 2014: 24th International Conference on Artificial Neural Networks, Hamburg, Germany, September 15 - 19, 2014 ; proceedings - Wermter, Stefan (Lecture notes in computer science, 2014)
The book constitutes the proceedings of the 24th International Conference on Artificial Neural Networks, ICANN 2014, held in Hamburg, Germany, in September 2014. The 107 papers included in the proceedings were carefully reviewed and selected from 173 submissions. The focus of the papers is on following topics: recurrent networks; competitive learning and self-organisation; clustering and classification; trees and graphs; human-machine interaction; deep networks; theory; reinforcement learning and action; vision; supervised learning; dynamical models and time series; neuroscience; and applications